Variability in the prescribing of intravenous fluids: A cross sectional multicentre analysis of clinical practice. (March 2018) - Ramsay, G.; Baggaley, A.; Vaughan Shaw, P.G.; Soltanmohammadi, E.; Ventham, N.; Guat Shi, Ng; Pearson, R.; Knight, S.R.; Forde, C.T.; Moore, N.; Kilkenny, J.; Clement, K.D.; et al.
Abstract: Aims: Intravenous (IV) fluid administration continues to be a mainstay of care in General Surgery. Yet if they are prescribed incorrectly significant morbidity including electrolyte abnormalities, renal impairment and cardiac failure can develop. Despite this, it is frequently the responsibility of the most junior staff to prescribe IV fluids. We aim to analyse the understanding of IV fluid prescribing amongst junior doctors and to describe variability in clinical practice. Methods: We undertook a multicentre questionnaire study. Foundation doctors and specialty trainees were invited to undertake a two part paper-based questionnaire. Part one analysed baseline knowledge of the concentration of commonly prescribed fluids. Part two consisted of four clinical vignettes requiring a IV fluid prescribing decision by the surveyed doctor. Results: A total of 143 Doctors working in 8 hospitals were recruited. 65 (45.5%) doctors correctly stated the daily maintenance fluid requirements of water for an adult (25–30 mls/kg/day), while only 54 (37.8%) knew the sodium concentration of 0.9% NaCl. Lack of postgraduate experience (p = 0.011), qualifying from a medical school outside the United Kingdom (p < 0.0001) and working in one of the eight hospitals in this study (p < 0.0001) were associated with a lower knowledge level. There was limited consensus in prescribing in the responses to the 4 clinical scenarios, with 69 unique combinations of fluid choice, rate and volume prescribed. Conclusions: Knowledge of the constituents of common IV fluids and routine requirement for fluid and common electrolytes is poor across junior doctors of all grades, driving large variation in clinical practice. Highlights: There remains significant variability in IV Fluid Prescribing. Education on this subject is lacking. This impacts on clinical care.